2008
DOI: 10.1007/s10903-008-9178-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Barriers that Reduce the Effectiveness of HIV/AIDS Prevention Strategies for Puerto Rican Women Living in Low-income Households in Ponce, PR: A Qualitative Study

Abstract: Background The HIV/AIDS epidemic has been strongly felt in Hispanic/Latino communities. Estimates of AIDS prevalence among Latinos in the US reveal that just nine States and the Commonwealth of Puerto Rico account for 89% of the Latinos living with AIDS in 2004. Previous research reveals social and cultural factors play an important role in HIV prevention. Methods Four focus groups were conducted, with 39 women, ages 21–67, participating in the discussions. The objectives of this research were to assess know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Other studies found that women who did report asking their partners to use condoms were met with refusal [78,84], mockery [84] and threatened abandonment [78]. In Nicaragua, while three women reported successfully convincing their partners to use condoms after their infidelity had been exposed, for two of them the condom use only lasted two weeks [84].…”
Section: Pathway 4 Women Experience Accusations Of Infidelity As a Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies found that women who did report asking their partners to use condoms were met with refusal [78,84], mockery [84] and threatened abandonment [78]. In Nicaragua, while three women reported successfully convincing their partners to use condoms after their infidelity had been exposed, for two of them the condom use only lasted two weeks [84].…”
Section: Pathway 4 Women Experience Accusations Of Infidelity As a Fmentioning
confidence: 99%
“…So when he wants to do [have sex] I make myself ready" [82] (p. 132) Some women blamed themselves for their partner's infidelity [80,81,84], demonstrating an internalization of patriarchal norms. In some studies, this was compounded by societal beliefs that men are unfaithful because women fail to meet their sexual needs at home, or are not 'desirable' enough to their husbands, forcing them to look for a sexual partner outside the marital relationship [78,80,84]. This quote exemplifies the stigma and discrimination many women faced because of their partner's infidelity due to patriarchal beliefs about male entitlement to sex, and the hopeless tone women took when discussing it.…”
Section: Pathway 4 Women Experience Accusations Of Infidelity As a Fmentioning
confidence: 99%
See 1 more Smart Citation
“…24 However, this may be because we identified and listed reasons for not using condoms and had the women select the reasons, giving them an “other” category and providing space for them to elaborate on the reason, whereas in the focus groups, the women all talked together and the moderator/facilitator was able to ask the women to explain their perceived barriers for engaging in safer sex, especially using or introducing condoms into their current relationships. 24 …”
Section: Discussionmentioning
confidence: 99%
“…24 These women noted feeling a lack of control over partner’s behavior, fear of physical violence, partner’s refusal to use a condom, and lack of negotiation skills. These data were collected through focus groups; the questions used to elicit the data were asked in a fairly general way (such as “What are the barriers to using condoms that you encounter in your sexual relationships?”).…”
Section: Previous Research Among Women Examining Reasons For Not Usinmentioning
confidence: 99%